EFFECT OF OCCLUSAL REDUCTION ON POST OPERATIVE PAIN IN PATIENT WITH SYMPTOMATIC PERIAPICAL PERIODONTITIS FOLLOWING ENDODONTIC INSTRUMENTATION- A RANDOMIZED CONTROL TRIAL - Qureshi, Rizwan; Abbasi, Abeera Faraz; Tariq, Hina; Majid, Nazish; Mushtaq, Farah; Niazi, Iffat Umair (Journal of Ayub Medical College Abbottabad, 2025)
Background: Post endodontic treatment pain is the most common complications within the first 72 hours. Various therapeutic modalities are used to reduce post endodontic pain, including use of NaOCl irrigant, long-acting anaesthetic, and preoperative drug delivery. One such techniques is to take the treated tooth completely out of occlusion. This study aimed to assess the effect of occlusal reduction versus no occlusal reduction on post endodontic pain. Methods: A randomized clinical trial was done from April 2024 to August 2024 in the operative dentistry department of Rawal Institute of Health Sciences, Islamabad. Sixty adult volunteers presented with symptomatic apical periodontitis for endodontic treatment and fulfilling the inclusion criteria were selected by convenience non-probability sampling. The patients were randomly divided into two groups, the occlusal reduction (OR) group and the no occlusal reduction (NOR) group, with 30 patients in each group. The patients of both groups were instructed to complete the VAS at 24 hours after the procedure to rate their pain as mild, moderate or severe and were asked to bring the Performa along at the next scheduled appointment. All the data collected was entered and analysed using (SPSS version 22.0). Chi-square test was used for qualitative variable (frequency of post-operative pain, gender) and independent sample T-test for quantitative variable (age). Results: There were 12 (40.0%) males in the non-occlusal group while 14 (46.6%) males in the occlusal reduction group. The majority of participants fell into the 18‒30 age range 12 (40.0%) in non-occlusal group and 11 (36.6%) in the occlusal reduction group. Average pain was significantly high in no occlusal reduction group (4.10±1.18 versus 2.11±1.00) and this difference was significant (p<0.001). This difference was also proven as per gender and age stratified analysis. Conclusion: Compared to non-occlusal reduction, the patients in occlusal reduction group had noticeably low pain scores.